Rendering a multi-dimensional problem space as an unfolding collaborative inquiry process. (July 2018) - Adams, Robin; Aleong, Richard; Goldstein, Molly; Solis, Freddy
Abstract : This study investigates a group working together in an authentic work setting as they collaboratively render a problem space. We employed an existing data set of a group designing for an European automaker. We used a collaborative inquiry paradigm as a lens for investigation. We analysed the dimensions of the problem space the group renders and the collaborative inquiry practices used. The group rendered a multi-dimensional problem space integrating user experience and organizational considerations for realizing user-centred products. We observed collaborative inquiry practices as four modes of evoking ways of knowing and two modes of building coherence. This study offers a new perspective on design as collaborative inquiry – a social process of building coherence to co-construct valid knowledge. Highlights: Shows problem framing as multi-dimensional connecting users, delivery, and organization. Demonstrates problem framing as collaborative inquiry to build coherence and valid knowledge. Expands and enriches an understanding of design as a social process.